Strategi Humas dalam Membangun Citra Madrasah Menjadi Mdarasah Unggulan di Kota Malang - Abie Maulana Al Givari (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2020)
This study aims to describe the public relations strategy in building the image of madrasas to become superior madrasahs in Malang City. This research was conducted in MAN 1 Malang City. This research was conducted using a qualitative descriptive approach, and in data collection researchers used interview techniques, observation and documentation study. The main subjects in this study are public relations, school principals, teachers and students. The results of this research are: 1) Public Relations publishes activities to be carried out by MAN 1 Malang City and the achievements achieved by MAN 1 Malang City to the community through online media 2) Public Relations collaborates with government agencies, education and non-educational institutions 3) Public Relations prepare high quality graduates in accordance with the vision of MAN 1 Malang City, namely